Sistem Pendukung Keputusan Penentuan Jurusan Pada Siswa Sma 1 Huluk Palik Menggunakan Php Dan Mysql - Yupianti, Yupianti; Utami, Feri Hari (Jurnal Media Infotama, 2020)
The Decision Support System for Determining Majors for students at State Senior High School 1 Huluk Palik, Sumber Rejo Village, North Bengkulu uses PHP and MYSQL for every second grade increase. The selection of majors is still manual. Teachers cannot yet measure students' abilities in terms of talent and academics. Sometimes teachers only measure in terms of report cards or class rankings. This certainly makes it difficult for students to enter majors according to their talents. Therefore, a decision support system application was created for student majors at State Senior High School 1 Huluk Palik, North Bengkulu using the Simple Additive Weighting (SAW) method. This system is designed using the PHP programming language and MySQL database. The resulting application can help North Bengkulu 1 Huluk Palik State High School in its student majors. The results of this application can present data quickly and provide information with a calculation process according to the highest normalization results on the results of the decision tree made and ultimately can make a decision.